URGENSI STUDI HADIS DI UIN SUMATERA UTARA - Agusman Damanik (SHAHIH (Jurnal Ilmu Kewahyuan), 2018)
“In its development to the present, the authenticity of tradition is often questioned. Much criticism is directed to the hadith, and some even reject it. That even though it has so long complemented the source of Islamic teachings (Qur'an), Hadith if it still needs to be tested its validity and validity. One of several causes is in addition to the absence of a firm guarantee of its validity, as well as the delay in writing the hadith itself. So it is very likely alleged transmission of many hadiths are false.”